Targeted quantification of N-1-(carboxymethyl) valine and N-1-(carboxyethyl) valine peptides of beta-hemoglobin for better diagnostics in diabetes - Jagadeeshaprasad, Mashanipalya G.; Batkulwar, Kedar B.; Meshram, Nishita N.; Tiwari, Shalbha; Korwar, Arvind M.; Unnikrishnan, Ambika G.; Kulkarni, Mahesh J. (Clinical Proteomics, 2016)
Background: N-1-(Deoxyfructosyl) valine (DFV) beta-hemoglobin (beta-Hb), commonly referred as HbA1c, is widely used diagnostic marker in diabetes, believed to provide glycemic status of preceding 90-120 days. However, the turnover of hemoglobin is about 120 days, the DFV-beta-Hb, an early and reversible glycation product eventually may undergo irreversible advanced glycation modifications such as carboxymethylation or carboxyethylation. Hence quantification of N-1-(carboxymethyl) valine (CMV) and N-1-(carboxyethyl) valine (CEV) peptides of beta-Hb would be useful in assessing actual glycemic status. Results: Fragment ion library for synthetically glycated peptides of hemoglobin was generated by using high resolution-accurate mass spectrometry (HR/AM). Using parallel reaction monitoring, deoxyfructosylated, carboxymethylated and carboxyethylated peptides of hemoglobin were quantified in clinical samples from healthy control, pre-diabetes, diabetes and poorly controlled diabetes. For the first time, we report N-1-beta-valine undergoes carboxyethylation and mass spectrometric quantification of CMV and CEV peptides of beta-hemoglobin. Carboxymethylation was found to be the most abundant modification of N-1-beta-valine. Both CMV-beta-Hb and CEV-beta-Hb peptides showed better correlation with severity of diabetes in terms of fasting glucose, postprandial glucose and microalbuminuria. Conclusions: This study reports carboxymethylation as a predominant modification of N-1-beta-valine of Hb, and quantification of CMV-beta-Hb and CEV-beta-Hb could be useful parameter for assessing the severity of diabetes.
Keywords: Diabetes; Diagnosis; Glycation; Glycemic control; HbA1c; Mass spectrometry

Autoantibodies against Nε-carboxymethyl lysine and methylglyoxal modified albumin are associated with cardiovascular risk in type 2 diabetes - Patil, Yugendra R.; Tiwari, Shalbha; Momin, Abdulrahaman A.; Unnikrishnan, A. G.; Kulkarni, Mahesh J. (International Journal of Diabetes in Developing Countries, 2025)
{Background Albumin is an abundant plasma protein which gets modified with advanced glycation end products (AGEs) predominantly in diabetic condition. AGE modification induces immune response and autoantibodies are generated which play an important role in disease pathology. Objective This study aimed to illustrate the role of autoantibodies against N epsilon-carboxymethyl lysine (CML) and methylglyoxal (MG) modified albumin in diabetic cardiovascular complications. MethodsType-2 diabetes subjects were enrolled and further grouped into stress test positive or stress test negative based on treadmill stress test (TMT). Autoantibody titer was quantified by ELISA assay for CML-modified albumin (stress test positive
Keywords: AGE; Atherosclerosis; Diabetes; Glycation; Immune response; ROC